The Conditions of the Resurrection in Tafsir and Hadith | أحوال القيامة في التفسير والحديث النبوي (دراسة موضوعية مقارنة) - Ade Pahrudin; Fadhilah Fakhrurrozi (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
This research aims to know the positions of the resurrection in the Tafsir of Al-Azhar and the interpretation of the Ruh al-Bayan and the hadith of the Prophet. In this research, the two researchers used an analytical approach, which is the analysis of some positions of the resurrection in Tafsir of Al-Azhar and the interpretation of the Ruh al-Bayan and the hadith of the Prophet. As for the method of this research, it is a library method, where the researchers collected information from sources and references related to the topic. One of the results of this research is that Sheikh Ismail Haqi al-Turki, who composed the interpretation of Ruh al-Bayan, is a Sufi exegesis, while the Indonesian Buya Hamka, who composed the interpretation of al-Azhar, is a literary exegesis. The two interpretations agree in most of the Qur’anic verses, and the difference may occur between them due to the different directions of their interpretation. The difference in style between the Prophet’s hadith and the Qur’anic verses in depicting the conditions of the Resurrection and its positions in the two things: First: The hadith focused on human conditions, while Qur’anic verses focus on the conditions of the universe. The second: The hadith used to depict the horrors of the Resurrection in clarifying the situations and consequences of the two sects: the believers and the unbelievers, and most of the Qur’anic verses portrayed the horrors of the Resurrection in exploding the world and the universe.